Biogenic Synthesis of Copper Oxide Nanoparticle from Aegle marmelos and its Anti-Cancerous Potential against HCT-116 Cell Line - Khamjan, Nizar A.; Farasani, Abdullah (Indian Journal of Pharmaceutical Education and Research, 2024)
Background and Aim Colorectal cancer stands as a frequently occurring fatal disease for several decades and the use of nanoparticles has long been explored in cancer treatments. Engineering the size and shape to attain an optimal efficacy of the nanoparticles and using a specific plant resource to enhance its compatibility to other healthy cell is a propitious approach. The present study investigates the anti-cancer activity of CuO NP synthesized from Aegle marmelos leaf extract against human colorectal cancer. Materials and Methods The CuO NPs (Nanoparticles) exhibited promising characteristics with UV and SEM-EDAX, its photochemical constituents were analyzed with FTIR, and the geometry of the synthesized nano-particles was studied using Zeta potential and particle size analyzer. The cell viability was scrutinized via trypan blue assay and further toxicity was determined by cell morphology and several in vitro analyses where the MTT assay presented that the 25 μg/mL of CuO NPs as the IC50 concentration. RESULTS The nuclear fragmentation was studied by DAPI staining which resulted in increased fluorescence of the treated cells indicating the robust effect of the CuO NPs and the mitochondrial damage was monitored through MMP analysis with declining fluorescence. The most vital aspect of understanding cancer pathogenesis is oxidative stress which was evaluated by ROS, NO, and LPO with favorable outcome. Conclusion The cell viability and ROS assay coalesce to suggest that CuO NPs indeed induce apoptosis and it is evident that Biogenically synthesized CuO NPs contain anti-proliferative potential and promotes apoptosis.
Keywords: Colorectal cancer; Aegle marmelos; Nanoparticles; Copper Oxide; Anti-cancer